Anaerobic poly-3-d-hydroxybutyrate production from xylose in recombinant Saccharomyces cerevisiae using a NADH-dependent acetoacetyl-CoA reductase - de las Heras, Alejandro Muñoz (Microb Cell Fact, 2016)
BACKGROUND: Poly-3-d-hydroxybutyrate (PHB) that is a promising precursor for bioplastic with similar physical properties as polypropylene, is naturally produced by several bacterial species. The bacterial pathway is comprised of the three enzymes β-ketothiolase, acetoacetyl-CoA reductase (AAR) and PHB synthase, which all together convert acetyl-CoA into PHB. Heterologous expression of the pathway genes from Cupriavidus necator has enabled PHB production in the yeast Saccharomyces cerevisiae from glucose as well as from xylose, after introduction of the fungal xylose utilization pathway from Scheffersomyces stipitis including xylose reductase (XR) and xylitol dehydrogenase (XDH). However PHB titers are still low. RESULTS: In this study the acetoacetyl-CoA reductase gene from C. necator (CnAAR), a NADPH-dependent enzyme, was replaced by the NADH-dependent AAR gene from Allochromatium vinosum (AvAAR) in recombinant xylose-utilizing S. cerevisiae and PHB production was compared. A. vinosum AAR was found to be active in S. cerevisiae and able to use both NADH and NADPH as cofactors. This resulted in improved PHB titers in S. cerevisiae when xylose was used as sole carbon source (5-fold in aerobic conditions and 8.4-fold under oxygen limited conditions) and PHB yields (4-fold in aerobic conditions and up to 5.6-fold under oxygen limited conditions). Moreover, the best strain was able to accumulate up to 14% of PHB per cell dry weight under fully anaerobic conditions. CONCLUSIONS: This study reports a novel approach for boosting PHB accumulation in S. cerevisiae by replacement of the commonly used AAR from C. necator with the NADH-dependent alternative from A. vinosum. Additionally, to the best of our knowledge, it is the first demonstration of anaerobic PHB synthesis from xylose. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12934-016-0598-0) contains supplementary material, which is available to authorized users.